Goosebumps. A night in Terror Tower [videorecording (DVD)] - Fruet, William, 1933-; Short, Kathryn, actress; Sevier, Corey, 1984-; Henderson, Rebecca; McGrath, Blake; Stine, R. L.; Stine, R. L. (Goosebumps., 2008)
A night in Terror Tower: Sue and Eddie are out sightseeing at the infamous Terror Tower when the wax figures in the Tower's torture chambers start to move. Suddenly the two are traveling back in time.